Language Learning Engagement Among Malaysian Undergraduates During MCO 1.0 - Soon, Chiow Thai; Loi, Chek Kim; Lau, Yoke Lian; Sabariah Abd Rahim; Siti Aishah Ramli (Secholian Publication, 2022)
The Covid-19 pandemic has changed the education practice in Malaysia. Online mode has become the new teaching and learning norm in Malaysia. This study applied the L2 language learning engagement to investigate the language engagement and motivation among the undergraduates in online language learning during the pandemic. The study was conducted in one of the local universities, the University of Malaysia Sabah as the research site. A survey by using questionnaire and interview session were administered to collect data for the study. The research sample of the study comprised of 42 respondents and five interviewees, and they were the second-year undergraduates. The research findings of the study showed i) the synchronized online classroom learning is the main platform for the undergraduates to practice their listening skill; ii) all the undergraduates practiced their speaking skill in language learning through online mode; iii) the reading material for the undergraduate students to practice their reading skill is related to the language lessons and preparation of course work and iv) the undergraduates write in the language they learnt when preparing for their course work and texting their language lecturers. The study also highlighted the Telco's played the most importance role in making the online teaching and learning successful.